Preventing heat stroke and heat illness on the workplace: a study on knowledge, attitudes and practices of safety representatives from Northern Italy (2016-2017). (13th November 2019) - Ricco, M; Vezzosi, L; Balzarini, F; Giosuè Mezzoiuso, A
Abstract: Introduction: Heatwaves (HWs) and rising environmental temperatures are significant health threats also for workplaces. This study will investigate knowledge, attitude and practices towards heat-related health issues in a sample of safety representatives from Northern Italy (SRs). Methods: A cross-sectional questionnaire survey was conducted in 2016-2017 among 327 SRs. Knowledge status was measured both in general and focusing on first-aid issues. Assessment of risk perception included severity and frequency of heat-related events. Multivariate logistic regression analysis assessed individual and work-related characteristics associated with SRs' risk perception. Results: 258 questionnaires were retrieved (participation rate 78.9%; mean age 48.2±25.2 years). Knowledge status was relatively good on technical/preventive issues (62.3%%±16.8) and first aid measures (67.1%±25.2), but a large share of respondents ignored the risk from exertional heat stroke (35.7%), and for heat strokes elicited by non-environmental heat (e.g. machineries, use of protective equipment, etc. 47.7%). The majority of respondents acknowledged the high frequency of HW events (90.7%), but only 44.6% agreed on their potential health threat. had received A specific first-aid formation was reported by 49.2% of respondents, while 10.9% had any previous interaction with heat-related disorders. Specific countermeasures had been put in place by parent company in 3.9% of cases. Eventually, previous participation to formation courses was associated with higher risk perception regarding severity and frequency of HW (OR 3.18 95%CI 1.40-7.23, OR 5.54 95%CI 1.59-19.23 respectively), while previous interaction with heat-related disorders apparently raised the perceived severity of heat-related health risk (OR 3.92 95%I 1.10-13.14). Conclusions: Although SRs exhibited a fairly good understanding of heat-related health issues on the workplaces, our findings also suggest the need to enforce specific countermeasures.